The initial and continuing training of geography teachers from the teaching reflection - Santos, Juanice Pereira; Sousa, Maria Solange Melo de (Revista Ensino de Geografia (Recife), 2020)
The article is the result of discussions with teachers of the Research Group, Teaching, Learning and Teacher Training (GEAF -UNB) that took place at the study meetings in 2019. The text analyzes the performance of the geography teacher in the classroom, with regard to initial and continuing education, the deficiency of knowledge and learning and the reflection of such weaknesses in the experiences experienced in the school routine.The theoretical contribution was basedon scientific documents of geography and education teaching, reflections of different authors: Cavalcanti (2017); Cunha (2010); Nóvoa (1992; 2004); Pimenta (2012); Shulman (2005); group readings and discussions; collection and recording of reports and interviews of geaf member teachers. At the end of the research, there are considerations regarding the main weaknesses in the educational process that interfere in the pedagogical practice of the geography teacher. The text also pointed out the importance of initial and continued training in order to qualify and transform teaching actions in the classroom.